Analisis Perputaran Piutang dan Perputaran Persediaan Terhadap Return On Assets - Yuli Surya Fauzia Pertami; Wiwin Sukiati; Lulu Kurnia Ningsih (Prodi Manajemen S1 dan D3 Keuangan & Perbankan, 2020)
Profitability ratios make it easy for companies to analyze a company's ability to earn and generate profits over time. The better profitability ratio, the better the ability to describe the company's high profitability. One of the profitability ratios, namely Return on Assets (ROA), is a ratio that shows how much the asset contributes to creating net income. The purpose of the research was to determine the effect of accounts receivable turnover and inventory turnover partially and simultaneously. The research methodology used is descriptive and associative . This research was conducted on the Manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2013-2017 was using purposive sampling. Based on the results of partial or t test, the variable accounts receivable turnover has a significant negative effect on Return on Assets (0,0028 < 0,05), while inventory turnover has no effect and is not significant for Return on Assets (0,1669 > 0,05). The results of research simultaneously or the F test, the variable receivable turnover and inventory turnover significantly influence profitability with the significancy value 0.006 < 0.05.